Acute-on-Chronic Liver Failure: Steps Towards Consensus - Loredana Gabriela Goran; Florina Alexandra Liţă (Cofaru); Carmen Fierbinţeanu-Braticevici (Diagnostics)
Acute-on-chronic liver failure (ACLF) is a clinical syndrome characterized by organ failure and high short-term mortality. Since its first definition in 2013, many international organizations have defined this syndrome and, till now, there has been no agreement regarding definitions and diagnostic criteria. Although the precise mechanism of ACLF is unknown, precipitant factors and the systemic inflammation response play a major role. Specific management of this high-mortality syndrome is still under development, but a general consensus in the diagnosis and management of ACLF is needed.